2013
DOI: 10.3168/jds.2012-6257
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and risk factors for lameness on organic and small conventional dairy farms

Abstract: Lameness is an important multifactorial disease that affects dairy cattle on both organic (ORG) and conventional (CON) farms. The objective of this study was to characterize perception of lameness and identify risk factors for lameness prevalence on ORG and similarly-sized CON farms. Dairy herds (n=292) were enrolled across 3 states (NY, OR, WI), with CON herds enrolled based on similar herd size and location of ORG herds. During a single herd visit, information was collected about management practices and lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 32 publications
3
19
0
3
Order By: Relevance
“…The prevalence of lameness observed for cattle in herds enrolled in this study was less than previously observed in studies that have used larger, more intensively managed herds (Cook, 2003;Fulwider et al, 2008) but only 43% of enrolled herds would have met the FARM and AHA requirements for lameness scores. Richert et al (2013b) previously reported that farmers enrolled in this study perceived less lameness than was observed by study personnel; thus, improved awareness of lameness is necessary to implement effective preventive management programs.…”
Section: Discussionmentioning
confidence: 92%
“…The prevalence of lameness observed for cattle in herds enrolled in this study was less than previously observed in studies that have used larger, more intensively managed herds (Cook, 2003;Fulwider et al, 2008) but only 43% of enrolled herds would have met the FARM and AHA requirements for lameness scores. Richert et al (2013b) previously reported that farmers enrolled in this study perceived less lameness than was observed by study personnel; thus, improved awareness of lameness is necessary to implement effective preventive management programs.…”
Section: Discussionmentioning
confidence: 92%
“…Es besteht die große Gefahr, dass das Ausmaß einer Lahmheitsproblematik in einem Betrieb dadurch deutlich unterschätzt wird. Da auch Landwirte dazu neigen, die Anzahl lahmer Tiere zu unterschätzen (16,39), kann dies zu chronischen und unter Umständen komplizierten Verläufen mit Abmagerung der betroffenen Tiere führen.…”
Section: Diskussionunclassified
“…Organic farms are generally associated with less frequent veterinary visits and use less outside support (e.g. nutritionist) than conventionally managed farms (Valle et al, 2007;CicconiHogan et al, 2013;Richert et al, 2013a) and so fewer veterinary-treated cases of disease are reported in organic than in conventional farms (Hardeng and Edge, 2001;Hamilton et al, 2002;Bennedsgaard et al, 2003;Valle et al, 2007;Mayen et al, 2010) and organic farmers are more likely to initiate therapy themselves (with no veterinarian involvement) using alternative treatments (Hamilton et al, 2002;Vaarst et al, 2006;Valle et al, 2007).…”
Section: Health Management In Small-scale Farmsmentioning
confidence: 99%